2004
DOI: 10.1007/s00134-004-2225-5
|View full text |Cite
|
Sign up to set email alerts
|

What is the daily practice of mechanical ventilation in pediatric intensive care units? A multicenter study

Abstract: One in every 3 patients admitted to the PICUs requires ventilatory support. The ARF was the most common reason for MV, and survival of unselected infants and children receiving MV for more than 12 h was 85%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
87
1
20

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 37 publications
9
87
1
20
Order By: Relevance
“…4 Farias et al observed acute respiratory failure as the cause for initiation of invasive ventilation in 72% of the cases. 5 Based on underlying disease etiology, bronchopneumonia with associated septic shock was the major condition which required invasive ventilation and also required a prolonged respiratory support of >72 hours. Valerie Payen et al in their study also observed that associated hemodynamic instability prolonged the duration of invasive ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Farias et al observed acute respiratory failure as the cause for initiation of invasive ventilation in 72% of the cases. 5 Based on underlying disease etiology, bronchopneumonia with associated septic shock was the major condition which required invasive ventilation and also required a prolonged respiratory support of >72 hours. Valerie Payen et al in their study also observed that associated hemodynamic instability prolonged the duration of invasive ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…6 Bousso et al remark that the difference in results could be reflecting the presence of populations with dissimilar characteristics. This is a common situation when analyzing studies conducted in South America, where there is a predominance of primary respiratory diseases 1,5,[8][9][10]14 compared to the United States or Europe, with predominance of elective surgical patients. 4,6,11,15 At this time, there still are no reliable criteria to predict which patients will require reintubation after tolerating a spontaneous breathing trial.…”
mentioning
confidence: 99%
“…Furthermore, this level of PEEP is often used within the pediatric age range. 24 Most studies show that the prone position alone does not alter cardiac output. In our experiments, although we did not measure cardiac output, MAP was constant for both groups, suggesting that cardiovascular hemodynamics were unaltered.…”
Section: Discussionmentioning
confidence: 99%